Concurrent Statistical Learning of Ignored and Attended Sound Sequences: An MEG Study - Daikoku, Tatsuya; Yumoto, Masato (Frontiers in Human Neuroscience, 2019)
In an auditory environment, humans are frequently exposed to overlapping sound sequences such as those made by human voices and musical instruments, and we can acquire information embedded in these sequences via attentional and nonattentional accesses. Whether the knowledge acquired by attentional accesses interacts with that acquired by nonattentional accesses is unknown, however. The present study examined how the statistical learning of two overlapping sound sequences is reflected in neurophysiological and behavioural responses, and how the learning effects are modulated by attention to each sequence. Statistical learning in this experimental paradigm was reflected in a neuromagnetic response predominantly in the right hemisphere, and the learning effects were not retained when attention to the tone streams was switched during the learning session. These results suggest that attentional and nonattentional learning scarcely interact with each other, and that there may be a specific system for nonattentional learning, which is independent of attentional learning.